COVID-19 and food allergy in children - D'Auria, Enza; Anania, Caterina; Cuomo, Barbara; Decimo, Fabio; Indirli, Giovanni Cosimo; Mastrorilli, Violetta; Santoro, Angelica; Sartorio, Marco U.A.; Veronelli, Elisabetta; Caffarelli, Carlo; Marseglia, Gian Luigi; Calvani, Mauro; et al. (Acta Biomedica Atenei Parmensis, 2020)
In children with food allergy the visits should be limited to those that are unequivocally needed on clinical basis. Food challenge can be performed in selected situations, taking a more detailed history to make sure that patients provide whatever information we need. The maintenance of a safe diet can be hampered by several factors. Nutritional supplementation may be necessary.